In search of conclusive evidence: How to test for adjustment to target capital structure - Hovakimian, Armen; Li, Guangzhong (Journal of Corporate Finance, 2011)
Simulation experiments show that both partial-adjustment and debt-equity choice models can generate spuriously significant estimates that are consistent with the hypothesis that firms have target debt ratios to which they periodically adjust. Regressions relying on full-sample fixed effects models of target leverage, in particular, produce results severely biased in favor of the target-adjustment hypothesis. Various target proxies and modifications to the standard methodologies are examined to identify partial-adjustment and debt-equity choice models that have power to reject the target-adjustment hypothesis. The resulting estimates of the speed of adjustment are in the range of five-eight percent per year.